Implementation of Character Education Based on the 9 Pillars of Character of the Indonesian Heritage Foundation - Tri Hastuti Rahmawati; dr. Reni Pawestuti Ambari Sumanto, M.K.M. (Universitas Negeri Semarang, 2025)
This research is based on TK Cahaya Rumah, which has been implementing character education based on the 9 pillars of IHF for 8 years and has been a coordinating school in the Limbangan District for 2 years. The purpose of this research is to explain the implementation of character education based on the 9 pillars of IHF character in children at TK Cahaya Rumah. This research uses a descriptive qualitative research type with an ethnographic method, employing data analysis techniques such as data reduction, data presentation, and conclusion drawing. The subjects of this research are school principals, teachers, and parents. The subjects of this research are school principals, teachers, and parents. The research results from the first problem formulation are (1) Planning, for learning planning, it is already provided by IHF. Starting from teaching modules, teaching media, supporting media, and much more. (2) Implementation, the implementation is already in accordance with what is in the IHF teaching module. There are 3 streams, namely a) special stream, b) integrated stream, c) co-parenting stream. (3) Evaluation, like planning, the evaluation is also already provided by IHF. The results of the questionnaire evaluation filled out by parents show that there is an influence from the implementation of character education based on the 9 pillars of character on children's character at TK Cahaya Rumah. The research results for the second problem formulation, namely supporting factors and inhibiting factors of the implementation of character education based on the 9 pillars of character IHF. There are two supporting factors, first, the competence possessed by educators and second, the cooperation between parents and teachers. The inhibiting factor of the implementation of character education based on the 9 pillars of character IHF at TK Cahaya Rumah is the child's home environment